2017
DOI: 10.1111/1756-185x.13131
|View full text |Cite
|
Sign up to set email alerts
|

Increased baseline RUNX2, caspase 3 and p21 gene expressions in the peripheral blood of disease‐modifying anti‐rheumatic drug‐naïve rheumatoid arthritis patients are associated with improved clinical response to methotrexate therapy

Abstract: Our results suggest that the expressions of MMP-9 and ULK1 might be associated with disease activity. Increased baseline gene expressions of RUNX2, p21 and caspase 3 in the peripheral blood might predict better responses to MTX therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…These findings are in accordance with [17] who suggested the important role of this osteoclastogenic factor in promoting osteoclasts formation and bone resorption, following MTX-chemotherapy. Moreover, [22] demonstrated that, MTX could increase osteoclasts density and reduce osteogenic differentiation; accompanied by reduction in mRNA expression of osteogenic factors. Similarly, [17] observed, upregulation of RANKL/OPG ratio and proinflammatory cytokines such as TNF-α, IL-1 and IL-6 in MTX-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with [17] who suggested the important role of this osteoclastogenic factor in promoting osteoclasts formation and bone resorption, following MTX-chemotherapy. Moreover, [22] demonstrated that, MTX could increase osteoclasts density and reduce osteogenic differentiation; accompanied by reduction in mRNA expression of osteogenic factors. Similarly, [17] observed, upregulation of RANKL/OPG ratio and proinflammatory cytokines such as TNF-α, IL-1 and IL-6 in MTX-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The same study also showed there was a significant positive correlation between caspase‐3 and Psoriasis Area and Severity Index score . In another case‐control study by Tchetina et al including 40 patients with rheumatoid arthritis, it was reported that runt‐related transcription factor 2, caspase‐3 and p21 gene levels were decreased after treatment and it was asserted that they could be used in the prediction of treatment response …”
Section: Discussionmentioning
confidence: 99%
“…Для этого необходимо провести исследование на когорте больных, которые ранее не получали данный препарат, определить экспрессию генов, обуславливающих воспаление, болевой синдром и/или разрушение суставов до и после терапии. Корреляционный анализ клинических данных больных после терапии с уровнем экспрессии генов данной когорты до терапии позволит выявить те гены, чья базальная экспрессия может свидетельствовать об эффективности применения терапевтического средства [152]. В дальнейшем, терапию данным препаратом следует проводить тем пациентам, у которых базальная экспрессия генов изменена соответствующим образом.…”
Section: анализ экспрессии генов в крови как инструмент персонифицироunclassified